2023
DOI: 10.3390/polym15020318
|View full text |Cite
|
Sign up to set email alerts
|

Liposomes or Extracellular Vesicles: A Comprehensive Comparison of Both Lipid Bilayer Vesicles for Pulmonary Drug Delivery

Abstract: The rapid and non-invasive pulmonary drug delivery (PDD) has attracted great attention compared to the other routes. However, nanoparticle platforms, like liposomes (LPs) and extracellular vesicles (EVs), require extensive reformulation to suit the requirements of PDD. LPs are artificial vesicles composed of lipid bilayers capable of encapsulating hydrophilic and hydrophobic substances, whereas EVs are natural vesicles secreted by cells. Additionally, novel LPs-EVs hybrid vesicles may confer the best of both. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 371 publications
0
11
0
Order By: Relevance
“…This could also have impacted the surface charge of EVs-DNZ due to changes in the proteins and/or lipids of the membrane exposed to the surface of the vesicles. 63 , 64 The zeta potential for NPs-PLA-PEG showed an overall negative charge without modification after drug loading. Low values of zeta potential (−40 mV) for both nanoformulations indicate reduced aggregation by the electrostatic repulsion of particles helping to increase physical stability.…”
Section: Discussionmentioning
confidence: 99%
“…This could also have impacted the surface charge of EVs-DNZ due to changes in the proteins and/or lipids of the membrane exposed to the surface of the vesicles. 63 , 64 The zeta potential for NPs-PLA-PEG showed an overall negative charge without modification after drug loading. Low values of zeta potential (−40 mV) for both nanoformulations indicate reduced aggregation by the electrostatic repulsion of particles helping to increase physical stability.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that PL is internalized, undergoes intracellular hydrolysis, and binds to the intracellular protein GSTP1 [ 68 ]. Also, multiple studies demonstrate cell-based drug internalization and loading into EVs, to generate EV-drug carriers [ 69 , 70 ]. To the best of our knowledge, this is the first time a natural product is shown to reduce the pro-oncogenic contents of retinoblastoma EVs with the ability to reduce proliferation in recipient cells.…”
Section: Discussionmentioning
confidence: 99%
“…They have similar properties to liposomes (e.g., structure, composition, drug loading, protection capacity, particle size, and pharmaco kinetics and pharmaco dynamics(PKPD), among others); however, they have limitations such as the inability to be mass-produced and a high cost. Hybrid vesicles synthesized from liposomes and extracellular vesicles have been developed as potential new delivery vehicles for pulmonary inhalation drug delivery [ 183 ].
Fig.
…”
Section: Delivery System For Pulmonary Drug Deliverymentioning
confidence: 99%